2017
DOI: 10.1177/2045893217716659
|View full text |Cite
|
Sign up to set email alerts
|

Combination targeted pulmonary hypertension therapy in the resolution of Dasatinib‐associated pulmonary arterial hypertension

Abstract: Dasatinib is a small-molecule tyrosine kinase inhibitor used in the treatment of hematological malignancies. Pulmonary arterial hypertension (PAH) is a rare but known complication. The mainstay of treatment is cessation of Dasatinib, and while clinical improvement is rapid, complete hemodynamic resolution of pulmonary hypertension (PH) still remains exceedingly uncommon. We present a case of Dasatinib-induced PAH in a woman with chronic myeloid leukemia, who demonstrated rapid and complete clinical and hemodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Another proposed mechanism is related to SRC family kinases and platelet-derived growth factor (PDGF) pathway [54,62,64]. SRC family kinases have a role in smooth muscle cells reproduction and also reducing pulmonary artery tone while their inhibition result in apoptosis and raised vascular resistance.…”
Section: Dasatinib-induced Pulmonary Arterial Hypertensionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another proposed mechanism is related to SRC family kinases and platelet-derived growth factor (PDGF) pathway [54,62,64]. SRC family kinases have a role in smooth muscle cells reproduction and also reducing pulmonary artery tone while their inhibition result in apoptosis and raised vascular resistance.…”
Section: Dasatinib-induced Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…It has been demonstrated that treatment with dasatinib causes a dose-dependent increase in production of mitochondrial ROS; resulting to endothelial apoptosis, pulmonary endothelial dysfunction and pulmonary hypertension. Another proposed mechanism is related to SRC family kinases and platelet-derived growth factor (PDGF) pathway [ 54 , 62 , 64 ]. SRC family kinases have a role in smooth muscle cells reproduction and also reducing pulmonary artery tone while their inhibition result in apoptosis and raised vascular resistance.…”
Section: Dasatinibmentioning
confidence: 99%
See 3 more Smart Citations